1986
DOI: 10.1136/bmj.292.6516.291
|View full text |Cite
|
Sign up to set email alerts
|

Acute fatty liver of pregnancy and diagnosis by computed tomography.

Abstract: A 39 year old woman was admitted to a maternity unit at 34 weeks' gestation with nausea, vomiting, and jaundice. Her condition deteriorated, and she was transferred to hospital, deeply unconscious and hypotensive. The diagnosis of acute fatty liver of pregnancy was initially suggested by the typical history of prodromal malaise and vomiting and the rapid onset of hepatic encephalopathy with profound hypoglycaemia and only small increases in transaminase activities. Computed tomography was performed: there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…This observation, com bined with other reports [6][7][8][9][10] that reduced liver CT numbers are obtained in acute fatty liver of pregnancy, led to the expectation that liver-spleen CT number ratios obtained in the early postpartum period in patients with HELLP syndrome would be substantially decreased. However, only 3 cases with more severe thrombocytope nia showed a slight decrease in liver-spleen CT number ratios, suggesting the presence of fatty liver [11], Although liver specimens were not obtained from any of our patients for ethical reasons [12], these 3 patients might have had livers with a wider distribution of relatively large fat droplets [5].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This observation, com bined with other reports [6][7][8][9][10] that reduced liver CT numbers are obtained in acute fatty liver of pregnancy, led to the expectation that liver-spleen CT number ratios obtained in the early postpartum period in patients with HELLP syndrome would be substantially decreased. However, only 3 cases with more severe thrombocytope nia showed a slight decrease in liver-spleen CT number ratios, suggesting the presence of fatty liver [11], Although liver specimens were not obtained from any of our patients for ethical reasons [12], these 3 patients might have had livers with a wider distribution of relatively large fat droplets [5].…”
Section: Discussionsupporting
confidence: 63%
“…Marked reductions in liver-spleen CT number ratios have been reported in acute fatty liver of pregnancy [6][7][8][9][10], but those patients experienced truly severe clinical conditions, such as jaundice, coagulopathy, mental deteri oration, and/or intrauterine fetal death. Their clinical condition could have been linked to a delay in medical intervention [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the present patient computed tomography and ultrasound examination did not establish the diagnosis of acute fatty liver of pregnancy. McKee et al (1986) reported that computed tomography established the diagnosis of acute fatty liver of pregnancy within three hours of admission because of acute hepatic failure, but the same examination did not show remarkable changes in liver eight days after delivery. In the present patient computed tomography was performed nine days after delivery when remarkable changes in liver might disappear.…”
Section: Discussionmentioning
confidence: 99%